Be the Captain, Not the Crew: Effective Development and Deployment of Artificial Intelligence in Marine Mammal Science - Ted Cheeseman; Brian Miller; Shyam Madhusudhana; Amanda Hodgson (Marine Mammal Science, 2026)
Machine learning (ML), particularly the availability of deep neural networks, has enabled the proliferation of modern artificial intelligence (AI) and has revolutionized data processing capacity in marine mammal science. The development and application of these systems has delivered 1000‐fold increases in throughput for applications such as photo identification and orders of magnitude increases in performance for passive acoustic detection of calls. Some AI systems now exceed the performance of human experts. As marine environments face unprecedented and compounding pressures from climate change, habitat degradation, and anthropogenic disturbance, these technological advances offer powerful promise. However, the success of AI applications depends less on algorithm sophistication than on the underlying information systems that enable their functionality. Here, we argue that marine mammal scientists must approach AI development with intentional agency—as captains rather than crew—emphasizing system‐level design, interpretability, human oversight, and collaborative frameworks. We examine the spectrum of AI capabilities today, from pattern recognition where ML excels to context judgments and value judgments which must remain defined and decided by humans. By designing AI systems that center domain expertise, prioritize accessibility, and facilitate community engagement, the marine mammal science community can harness computational power while maintaining scientific rigor and advancing equitable conservation outcomes.

Total Numbers and Movements of Photo‐Identified Subantarctic (Type D) Killer Whales - Jared R. Towers; Paul Tixier; Christophe Guinet; Nicolas Gasco; John P. Y. Arnould; Ted Cheeseman; Robert L. Pitman (Marine Mammal Science, 2026)
The distinctive Subantarctic (Type D) killer whale (DKW) ( Orcinus orca ) is a highly divergent and apparently inbred form previously known only from three mass strandings and several dozen at‐sea sightings, primarily from Patagonian toothfish ( Dissostichus eleginoides ) longline vessels in the southern Indian Ocean and from tourism vessels in the Scotia Sea. Its range appears to be circumpolar throughout the Subantarctic, but very little is known about total numbers and overall movements. We summarize photo‐identification data from 352 of 406 sightings collected between 44° S and 62° S from 2003 to 2024. Among 207 photo‐identified individuals there were two distinct clusters of 78 and 29 toothfish depredators, one in the southern Indian Ocean and the other off southern Chile, respectively. An additional 100 DKW were photo‐identified throughout the wider Subantarctic. Discovery curves indicate that DKW may be more abundant than some less divergent or inbred killer whale populations. Depredating DKW showed seasonal and interannual site fidelity, but 10 depredating individuals identified in the southern Indian Ocean were also resighted in the southern South Atlantic, 4428 km away. Probable re‐sightings of two other DKW occurred in the Scotia Sea over distances of 1070 and 41 km, respectively. These latitudinally narrow, long‐distance inter‐ocean movements are unique among killer whales. During the study period, the entirely pelagic distribution of encounters appears to have shifted significantly southward.

Evaluating the Effectiveness of a Multispecies Matching Algorithm Applied to a Novel Species, Risso's Dolphins ( Grampus griseus ) - Alexandra Vanderzee; Ted Cheeseman; Philip T. Patton; John Calambokidis (Marine Mammal Science, 2026)
Automated matching algorithms are an increasingly valuable tool in marine mammal research. A multispecies matching algorithm, originally described in Patton et al. analyzes distinctive morphological characteristics on cetaceans using scarring, pigmentation patterns, and notches along the trailing edge of the dorsal fin, which can pose challenges in traditional eye‐based matching due to individual variation over time. While the algorithm was trained on 24 different cetacean species, Risso's dolphins were not included. Here, we assess its effectiveness using Cascadia Research's Risso's dolphin photo‐identification catalog, which consists of 1165 unique individuals from Southern California documented across 701 sightings from 2010 to 2021. The multispecies algorithm identified 90 missed matches within the catalog and was subsequently used to update the Cascadia Research catalog more efficiently with sightings collected through 2024. Our results indicate that the algorithm outperformed experienced human matchers, particularly for individuals with less distinctive features, streamlining the identification process and supporting the long‐term monitoring of Risso's dolphins while showing strong potential for application to other species with similar identification challenges.

Optimizing automated photo identification for population assessments - Philip T. Patton; Krishna Pacifici; Robin W. Baird; Erin M. Oleson; Jason B. Allen; Erin Ashe; Aline Athayde; Charla J. Basran; Elsa Cabrera; John Calambokidis; Júlio Cardoso; Emma L. Carroll; et al. (Conservation Biology, 2025)
Several legal acts mandate that management agencies regularly assess biological populations. For species with distinct markings, these assessments can be conducted noninvasively via capture‐recapture and photographic identification (photo‐ID), which involves processing considerable quantities of photographic data. To ease this burden, agencies increasingly rely on automated identification (ID) algorithms. Identification algorithms present agencies with an opportunity—reducing the cost of population assessments—and a challenge—propagating misidentifications into abundance estimates at a large scale. We explored several strategies for generating capture histories with an ID algorithm, evaluating trade‐offs between labor costs and estimation error in a hypothetical population assessment. To that end, we conducted a simulation study informed by 39 photo‐ID datasets representing 24 cetacean species. We fed the results into a custom optimization tool to discern the optimal strategy for each dataset. Our strategies included choosing between truly and partially automated photo‐ID and, in the case of the latter, choosing the number of suggested matches to inspect. True automation was optimal for datasets for which the algorithm identified individuals well. As identification performance declined, the optimization recommended that users inspect more suggested matches from the ID algorithm, particularly for small datasets. False negatives (i.e., individual was resighted but erroneously marked as a first capture) strongly predicted estimation error. A 2% increase in the false negative rate translated to a 5% increase in the relative bias in abundance estimates. Our framework can be used to estimate expected error of the abundance estimate, project labor effort, and find the optimal strategy for a dataset and algorithm. We recommend estimating a strategy's false negative rate before implementing the strategy in a population assessment. Our framework provides organizations with insights into the conservation benefits and consequences of automation as conservation enters a new era of artificial intelligence for population assessments.

First documented movement of wild killer whales ( Orcinus orca ) between Iceland and Norway - Marie‐Thérèse Mrusczok; Emma Luck; Ted Cheeseman; Jamie Coleman; Javier Cotín; Andrew Peacock; Robert A. Stefansson; Menja von Schmalensee (Marine Mammal Science, 2025)

Integrating the needs of recovering populations of baleen whales into the revised management framework for the commercial fishery for Antarctic krill - Philip N. Trathan; Matthew S. Savoca; Ari Friedlaender; Mick Baines; Elke Burkhardt; Ted Cheeseman; Luciano Dalla Rosa; Helena Herr; Eduardo R. Secchi; Alexandre N. Zerbini; Ryan R. Reisinger (Frontiers in Marine Science, 2024)
We consider how the ongoing recovery of baleen whale populations requires improved understanding when managing the largest commercial fishery in the Southern Ocean, the fishery for Antarctic krill. Baleen whales already represent one of the major consumers of krill, and as such compete with the fishery. However, they are not explicitly included either in the monitoring programme or the krill fisheries management approach of the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR). Individual baleen whales are at direct mortality risk from ship strike, entanglement, or by-catch. In addition, sub-lethal impacts on individuals, albeit with population-level consequences, via decreased body condition and reproductive rates, may arise from local depletion of prey and prey-field disturbance that increases whale energetic costs. Mitigating these risks requires that baleen whales, including those species not yet recovered, are fully integrated into management procedures. A vital issue will be to facilitate the ongoing recovery of blue, fin and sei whales, populations of which are still heavily depleted relative to their pre-whaling abundance. Part of the answer to this will be how CCAMLR resolves outstanding issues related to its newly emerging revised krill fishery management framework. Management of the krill fishery is data-poor, with much of the scientific support reliant upon data that are now decades old. The decision rules for determining sustainable yields need careful re-evaluation, given they were negotiated at a time when baleen whales were rarely observed, and krill fishery catches were low in relation to the estimated available krill biomass. The Antarctic marine ecosystem is spatially and temporally dynamic, and is changing, yet CCAMLR still assumes a static system. An explicit commitment to collect up-to-date monitoring data about krill and baleen whales is vital to help inform the revised management framework. Precaution argues that catch levels should not increase until adequate data are available for effective management. Knowledge about the status of baleen whales will inevitably require close collaboration with the International Whaling Commission.

Photo‐identification and satellite telemetry connect southern right whales from South Georgia Island (Islas Georgias del Sur) with multiple feeding and calving grounds in the southwest Atlantic - Amy S. Kennedy; Emma L. Carroll; Alexandre N. Zerbini; C. Scott Baker; Manuela Bassoi; Nazarena A. Beretta; Danielle L. Buss; Susannah Calderan; Ted Cheeseman; Martin A. Collins; Paula Costa‐Urrutia; Paul Ensor; et al. (Marine Mammal Science, 2024)
The sub‐Antarctic waters of South Georgia Island (Islas Georgias del Sur, SG/IG) are a regularly visited feeding ground for southern right whales ( Eubalaena australis , SRW) in the southwest Atlantic. Satellite telemetry and photo‐identification records were compared to better understand the role of SG/IG in the SRW migratory network. We present the first insights from SRW satellite‐tracked from the SG/IG feeding ground, habitat use patterns in the Scotia Arc, and movements to Antarctic habitats. Photo‐identification comparisons to calving and feeding areas across the South Atlantic and a review of sightings of cetaceans reported from Bird Island (west of SG/IG) since 1979 illuminate long‐term habitat use patterns in SG/IG. We present the first recorded migratory movement between SG/IG and multiple countries: Argentina, Uruguay, and Brazil. Photo‐identification (1) linked SG/IG to a female SRW with a long‐term sighting history in Brazil, and (2) provided the first match between SG/IG and the western Antarctic Peninsula, suggesting the latter could extend the feeding area for southwest Atlantic SRW. Satellite tracking and opportunistic sightings suggest that shelf and coastal waters west of SG/IG represent an important multi‐season SRW feeding habitat and add to our overall understanding of habitats and ranges occupied by recovering southwest Atlantic SRW.

The most southerly occurrence of humpback whales in the western Weddell Sea - Angus F. Henderson; Ted Cheeseman; Nadia Curcio; Maria L. Marcías; Olive Andrews; Mary‐Anne Lea (Marine Mammal Science, 2023)

Towards the definition of the humpback whale population units along the Mexican and Central American coasts in the Pacific Ocean - Pamela Martínez‐Loustalot; Katherina Audley; Ted Cheeseman; Joëlle De Weerdt; Astrid Frisch‐Jordán; Oscar Guzón; Marilia Olio; Christian D. Ortega‐Ortiz; Nicola Ransome; Francisco Villegas‐Zurita; Jorge Urbán R. (Marine Mammal Science, 2023)
The SPLASH project (2004–2006) revealed complex population structure and migratory connections, but no regional effort was made along the southern Mexican Pacific coast until dedicated research was initiated in 2010. It is unclear whether humpback whales documented in this region belong to the Mexican or Central American population units. This study aimed to establish the relationship between humpback whales of southern Mexico and those of the surrounding population units. Humpback whale photo‐identification images were compared from multiple locations in north, central, and southern Mexico and Central America. Whales' movements among regions were estimated using the Interchange Index ( InI ) and the Movement Index ( MI ). The results showed higher movements among the southern sampling areas, suggesting that whales from southern Mexico belong to the “Central American population unit.” This population unit migrates north to the feeding areas of the US West Coast using a migratory corridor along mainland Mexico to the mouth of the Gulf of California along the Baja California Peninsula. The degree of interaction with humpback whales from other population units is unknown. More studies are needed to understand population structure and disentangle photographic capture of whales on migration from whales where this is their main wintering area.

Movements and residency of fin whales (Balaenoptera physalus) in the California Current System - Erin A. Falcone; Erin L. Keene; Eric M. Keen; Jay Barlow; James Stewart; Ted Cheeseman; Craig Hayslip; Daniel M. Palacios (Mammalian Biology, 2022)

From the Antarctic Peninsula to eastern Australia: the longest migration of a humpback whale through the South Pacific Ocean - Jorge Acevedo; Anelio Aguayo-Lobo; Peta Beeman; Ted Cheeseman; Carlos Olavarría (Mammalian Biology, 2022)

Advanced image recognition: a fully automated, high-accuracy photo-identification matching system for humpback whales - Ted Cheeseman; Ken Southerland; Jinmo Park; Marilia Olio; Kiirsten Flynn; John Calambokidis; Lindsey Jones; Claire Garrigue; Astrid Frisch Jordán; Addison Howard; Walter Reade; Janet Neilson; et al. (Mammalian Biology, 2022)

First humpback whale (Megaptera novaeangliae) re-sighting between Azorean waters and the Barents Sea (Murman coast, northwestern Russia) - Rui Peres dos Santos; Rafael Martins; Anton Chaiko; Ted Cheeseman; Lindsey S. Jones; Frederick W. Wenzel (Polar Biology, 2022)

Low Resighting Rate of Entangled Humpback Whales Within the California, Oregon, and Washington Region Based on Photo-Identification and Long-Term Life History Data - Jennifer Tackaberry; Elana Dobson; Kiirsten Flynn; Ted Cheeseman; John Calambokidis (Frontiers in Marine Science, 2022)
Bycatch, commonly referred to as entanglement, is a leading source of human-caused mortality of baleen whales. A better understanding of the individuals that survive (or perish from) their entanglement can help reduce the risk of bycatch by informing gear modifications and fisheries management. However, determining survival rates is restricted by the ability to track individuals once they become entangled. Historically, the effort to identify and resight individuals from known entanglement cases was low along the West Coast. The recent increase of entanglements and photo-identification efforts in the California, Oregon, and Washington region provides an opportunity to assess entangled humpback whales’ resighting rates to better understand the effect of entanglements from the individual to the population level. We used photo-ID images of entangled humpback whales between 1982 and 2017 to examine pre- and post-entanglement sighting histories from longitudinal catalogs and life history data (Cascadia Research and Happywhale). We compared the entangled whales ( n = 37) against control whales ( n = 2,296), selected based on the date and location of the entanglement reports, to evaluate the deviation from the expected mortality rates (or lack of resighting) caused by entanglements and to help inform/support/test National Oceanic and Atmospheric Association’s Serious Injury and Mortality (SI/M) index. Our results suggest that entangled whales were resighted less often than the control groups. Entangled whales with short pre-entanglement sighting histories and without post-entanglement resights did not match other feeding ground populations. Therefore, the higher proportion of entanglements with shorter sighting histories is likely due to their being alive for fewer years, indicating a higher risk of entanglement for younger whales. This indicates that entangled humpback whales may not be as large or strong as mature individuals, and future gear modifications should reflect that possibility. Additionally, the severity of the initial SI/M score aligned well with our resighting rates, though this worsened with the final score assigned. Continued effort to gather and improve data collection about entanglements will help enhance the SI/M determinations. Our findings show the value of photo-identification of entangled whales and how it dramatically increases our understanding of entanglements.

First evidence of interchange of humpback whales (Megaptera novaeangliae) between the Magellan Strait and Antarctic Peninsula feeding grounds - Jorge Acevedo; Juan Capella; Ted Cheeseman; Cole C. Monnahan; Ken Southerland; Paola Acuña; Anelio Aguayo-Lobo (Polar Biology, 2021)

Northernmost records of Southern Hemisphere humpback whales ( Megaptera novaeangliae ) migrating from the Antarctic Peninsula to the Pacific coast of Nicaragua - Joëlle De Weerdt; Eric Angel Ramos; Ted Cheeseman (Marine Mammal Science, 2020)